The Role of Pelvic and Perineal Muscles in Reproductive and Excretory Functions - Martínez-Gómez, Margarita; Corona-Quintanilla, Dora Luz; Cruz-Gómez, Yolanda; Zempoalteca, René; Rodríguez-Antolín, Jorge; Castelán, Francisco (IntechOpen, 2012)
None